The Role of The Nahdlatul Ulama Agricultural Development Institute in Empowering Millennial Farmers to Strengthen Food Security in Pati Regency - Kamto Kamto; Muntaha Luthfi (Empower : Jurnal Pengembangan Masyarakat Islam, 2026)
The Nahdlatul Ulama Agricultural Development Institute (LPPNU) plays a strategic role in empowering millennial farmers to strengthen regional food security. This study aims to analyze and describe the LPPNU empowerment model in supporting millennial farmers in Pati Regency. The study employed descriptive qualitative and quantitative approaches, with data collection techniques including interviews, observation, questionnaires, and documentation. The research subjects included LPPNU administrators, partner institutions, and millennial farmers participating in the LPPNU mentoring program. Data analysis was conducted using descriptive statistics and the stages of reduction, presentation, and conclusion drawing. The results indicate that the LPPNU empowerment model was developed through four main, complementary models: the participatory model, the technology and innovation model, the institutional and network model, and the social entrepreneurship model. The participatory model performed very well, marked by the high level of involvement of millennial farmers in all stages of the empowerment program. The technology and innovation model encouraged increased efficiency and productivity through the use of appropriate agricultural technology. Meanwhile, the institutional and network model strengthened partnerships and farmers' access to resources, while the social entrepreneurship model increased value added and economic independence for millennial farmers. Overall, the implementation of LPPNU empowerment has been shown to significantly increase the capacity of millennial farmers and strengthen food security in Pati Regency by increasing production, diversifying food, and strengthening the local agricultural economy.